Modeling and analysis of conducted EMI for switching power supplies - Pattabhiraman Sridhar. (2008)
This project analyzes the conducted emissions from SMPS and presents a systematic approach to designing a power line filter for the same. The approach used here prevents over design of the filter and thus reduces the product cost.